Genetic diversity of Capsicum pubescens by functional genomic markers of CYP450 - Escalera-Ordaz, Ana Karen; Guillén-Andrade, Héctor; López, Pedro Antonio; Tapia Vargas, Luis Mario (Revista Mexicana de Ciencias Agrícolas, 2024)
The research work was developed at the Plant Genetic Resources Laboratory of the ‘Presidente Juárez’ Faculty of Agrobiology of the Michoacán University of San Nicolás de Hidalgo, in 2019 and 2022. The aim of this research was to evaluate the usefulness of functional markers derived from CYP450 for genetic diversity studies in Capsicum pubescens. The genetic material consisted of 31 cultivated varieties of C. pubescens from three different localities in the state of Michoacán, Mexico. Genomic DNA was obtained based on the protocol of Huang et al. (2013) and two combinations of CYP450 primers were included in the analysis. The amplification products were separated on 8% acrylamide gels and stained with silver nitrate. A total of 85 loci were detected: the CYP2B6F/CYP2C19R combination detected 34 polymorphic loci, while the CYP2C19F/CYP1A1R combination detected only 27. The diversity analysis of C. pubescens identified 1.54 alleles per locus, 1.33 effective number of alleles per locus, Shannon index of 0.3, a heterozygosity index of 0.2 and 60.39% of polymorphic loci. The results obtained show that markers derived from CYP450 are an efficient and low-cost alternative for studies of genetic diversity in plant species.
Keywords: Capsicum pubescens; genetic variability